A multicentre, open‐label study of emicizumab given every 2 or 4 weeks in children with severe haemophilia A without inhibitors. Issue 6 (12th September 2019) - Shima, Midori; Nogami, Keiji; Nagami, Sayaka; Yoshida, Seitaro; Yoneyama, Koichiro; Ishiguro, Akira; Suzuki, Takashi; Taki, Masashi
Abstract: Introduction: Emicizumab is a recombinant humanized bispecific monoclonal antibody mimicking the cofactor function of activated factor VIII. Aim: In this multicentre, open‐label study (HOHOEMI), we evaluated the efficacy, safety and pharmacokinetics of emicizumab in Japanese paediatric patients aged <12 years with severe haemophilia A without factor VIII (FVIII) inhibitors. Methods: Emicizumab was administered subcutaneously, with four loading doses of 3 mg/kg every week followed by maintenance doses of 3 mg/kg every 2 weeks (Q2W) or 6 mg/kg every 4 weeks (Q4W) in 6 and 7 patients, respectively. Results: All patients completed at least 24 weeks of treatment. Baseline ages ranged from 4 months to 10 years, and all patients had been treated with FVIII prophylaxis prior to enrolment except a 4‐month‐old patient untreated with FVIII previously. In the respective Q2W and Q4W cohorts, 2/6 and 5/7 patients experienced no treated bleeding events, and annualized bleeding rates for treated bleeding events were 1.3 (95% confidence interval [CI], 0.6‐2.9) and 0.7 (95% CI, 0.2‐2.6). All caregivers preferred emicizumab to the patient's previous treatment. Only one related adverse event (injection site reaction) was observed. There were no thromboembolic events or thrombotic microangiopathy. Individual trough plasma concentrations of emicizumab were within the variability observed in preceding adult/adolescent studies. All patients tested negative for anti‐emicizumab antibodies. Conclusions: Emicizumab administered Q2W or Q4W was efficacious and safe in paediatric patients with severe haemophilia A without inhibitors. This study was registered at http://www.clinicaltrials.jp (JapicCTI‐173710).